URGENSI PEMIKIRAN SISTEM PERTANIAN BERKELANJUTAN - Sarea - (Teknosains, 2011)
Agriculture paradigm which during the time still more amount base on by economic neo-klasik strength. Paradigm which see agriculture as economic activity produce, needing a number of factors production to yield the certain production amount. Agriculture system  have continuation to agriculture system which not destroy the nature, balancing and environmental continuity. In this context, continueing agriculture is resources management not only succes in fulfilling requirement of human being food, but also maintain or preserve the experienced resource. So sustainable syatem is agriculture system which not merely addressed in fulfilling requirement of human being food, but also maintain or preserve the experienced resource. Agriculture System  have convergent continuation at three based, that is economic continueing, social continueing, and ecology ( environ-mental) continueing. Keyword: Agriculture, sustainable, enviromental